Biomechanical Analysis of Various Connector Designs of Dental Implant Complex: A Numerical Finite Element Study - Shawkat A Elsheikh; Mohamed I El-Anwar; Tao Hong; Christoph Bourauel; Abdulaziz Alhotan; Noha M Anany; Islam G Shahin; Al-Hassan Diab; Tarek M Elshazly (International Dental Journal)
Objective: To evaluate the biomechanical behavior of 5 types of commonly used implant/abutment connectors, using Finite Element Methods (FEM). Methods: Five models of implant-abutment connections were designed using computer-aided design (CAD) software: Tri-channel (M1), Conical internal hexagon (M2), Morse taper with an integrated screw (M3), Internal hexagon (M4), and Tube-in-tube (M5). The bone was modeled as coaxial cylinders, with the inner cylinder representing spongy bone and the outer 1 mm-thick cylinder representing cortical bone. A premolar crown geometry was designed onto the abutment with a 40 µm-thick cement layer. Three loading scenarios were applied to each model: (1) a 100 N compressive load, (2) a 50 N oblique load at 45° (relative to the implant axis), and (3) a 50 N lateral load. Results: All stress and deformation values remain within the tolerable limits for the materials used. Notably, M1, M4, and M5 exhibited optimal biomechanical performance. M1 and M4 recorded the lowest stresses in implant components, 24.4 to 24.8 MPa in the abutment and 27.5 to 27.9 MPa in the screw under compression, along with minimal crown deformation (8.6 µm compared to M3’s 11.7 µm). In contrast, M3 experienced the highest implant-component stresses (68.5 MPa in the abutment and 120.2 MPa in the screw) but showed the lowest cortical bone stress at 7.7 MPa, versus 10.2 MPa in M4. Conclusion: For long-term durability, implants with an internal hexagon (M4) or tri-channel (M1) design are preferable, as they minimize stress and deformation within the implant complex, thereby reducing the risk of prosthetic failure. While the Morse taper (M3) design may benefit patients with compromised bone density, its higher implant-component stresses warrant caution. Clinical significance: This study provides valuable insights to support evidence-based selection of implant–abutment connection designs. Among the 5 evaluated systems, the Tri-channel (M1) and Internal Hexagon (M4) designs demonstrated superior biomechanical performance by minimizing stress concentrations within the implant components and surrounding bone. These configurations are therefore recommended for routine clinical use to enhance prosthetic stability, reduce the likelihood of mechanical complications such as screw loosening or fracture, and prolong implant longevity. Conversely, although the Morse Taper with integrated screw (M3) design showed the lowest stress on cortical bone – suggesting potential benefit for patients with reduced bone quality – it exhibited the highest stress levels within implant components, indicating a higher mechanical failure risk. Clinicians should weigh these biomechanical trade-offs when planning treatment, particularly in patients with high functional loads or compromised bone conditions.